Smith & Keenan's English Law : Text and cases. - Wild, Charles (Law teacher); Weinstein, Stuart; Smith, Kenneth, 1910-1966.; Keenan, Denis J. (Harlow : Longman, 2010)
This book takes account of changes to the law including new statutory provisions and cases. In order to keep users up to date with current developments, there is a bulletin service for tutors and lecturers.
Previous ed.: published as by Denis J. Keenan. 2007.
Includes index.
Keywords: Law -- England; Law -- Wales; Law